Perceptions and Attitudes Toward COVID-19-Related National Response Measures of Vietnamese: Implications for Pandemic Prevention and Control - Nguyen, Thao Thi Phuong; Nguyen, Long Hoang; Le, Huong Thi; Vu, Giang Thu; Hoang, Men Thi; Nguyen, Diep Ngoc; Le, Xuan Thi Thanh; Tran, Bach Xuan; Nguyen, Thao Thanh; Pham, Quan Thi; Ta, Nhung Thi Kim; Nguyen, Quynh Thi; et al. (Frontiers in Public Health, 2020)
Introduction: Public perceptions and attitudes toward preventive and control measures are vital to ensure the success of national response strategies in combating COVID-19. This study assessed perceptions and attitudes via the importance of national response measures to COVID-19 among people under the nationwide partial lockdown of Vietnam. Methods: An online cross-sectional survey was conducted on 1382 people in Vietnam. Perceptions and attitudes toward seven national response measures to COVID-19 epidemics were assessed. Multivariable Tobit regression models were employed to identify factors associated with the perceptions. Results: The proportion of participants strongly agreeing with the measure “Isolate people from abroad and people in contact with people infected with COVID 19” was the highest (96.9%), following by the measure “Obligatory to wear face masks in public places” (96.8%), and “Blockade of places having new cases” (92.9%). Living in the Southern region, having a family with more than 5 people, and having postgraduate education were negatively correlated to the levels of perceived importance of “Social distancing and community screening” measures. Meanwhile, having postgraduate education (Coef.=-0.04; 95%CI: -0.07; -0.01), working as white-collar workers (Coef.=-0.04; 95%CI: -0.08; -0.01), and having fixed-term full-time employment (Coef.=-0.07; 95%CI: -0.10; -0.03) were inversely associated with the levels of perceived importance of the “Mandatory quarantine and personal protective equipment” measures. Conclusion: This study informed highly positive perceptions and attitudes toward the national response measure to combat the COVID-19 in Vietnam. Contextualized strategies to maintain and improve these perceptions are warranted to ensure the success of preventive measures in the future.